P1251 Percutaneous closure of two mitral perivalvular leaks: when the imaging guides the hands during threatening complications. (17th January 2020) - Cocco, D; Melillo, F; Pannone, L; Ruggio, A; Stella, S; Ingallina, G; Capogrosso, C; Ancona, F; Montorfano, M; Agricola, E
Abstract: With the contemporary development of structural interventional cardiology the prevalence of perivalvular leaks (PVL) is expected to grow. Advanced multimodality imaging is necessary for the guidance of transcatheter closure of PVL. We describe the case of a 57 year-old woman who underwent transcatheter mitral PVL closure. Past clinical history included a lymphoma treated with chemio and radiotherapy. Six months before she underwent a surgical replacement of the aortic and mitral valves with two mechanical prosthesis for severe aortic and mitral stenosis. Because of the calcium burden in both the annuluses, undersized mitral valve prosthesis was implanted leading to the presence of two moderate mitral PVL. The patient subsequently required hospitalization for acute HF and hemolytic anemia and received multiple blood transfusions. TEE confirmed the presence of a large antero-lateral PVL and a small medial PVL (3D VCA 0, 32 cm2 and 0, 2 cm2 respectively, associated with reverse flow in the pulmonary veins) with an extension of 33% of the circumference of the prosthesis. The regurgitation was considered severe and a percutaneous closure was planned with 3D-TEE and fluoroscopy image fusion guidance. Under general anesthesia a transeptal puncture was performed and the medial leak was closed with two vascular plugs (6mm each). During the deployment of the plugs an intermittent blockage of the medial disk of the prosthesis was noticed, which resolved completely after the removal of the wires previously positioned for the engagement of the leak. The lateral leak was then engaged and a second plug (10mm) was advanced causing a discontinuous interference with the two disks. The direct interference with the lateral disk caused a blockage in the closing position (leading to moderate stenosis, medium gradient 7mmHg) and in the opening position (leading to a massive regurgitation). The medial disk was intermittently blocked in the closing position due to the bulky effect of the devices provoking a traction and displacement of the prosthesis towards the medial region of the valve. To avoid this interference the plug was released with a marked atrial protrusion. Notably, after the removal of the wires no malfunctioning of the disks was noticed and the mild residual shunts appeared further decreased. The procedure was considered successful and at follow-up no residual leak was found. The percutaneous closure of PVL is a safe and effective intervention. Multimodality imaging is essential for the diagnosis, planning and procedural guidance. The knowledge of possible complications is warranted for the achievement of an optimal result. This case clearly show the possibility of interference with the prosthesis and overestimation of residual leaks.